Prevalence of bronchiolitis in patients with Rheumatoid arthritis - Khusainova, Munira Alisherovna; Khaydarov, Sanjar Nizamitdinovich; Makhmudova, Khanuza Davranovna; Nayimov, Abror Shokirovich (Science and Education, 2023)
Inflammation of the bronchioles is common in various diseases. The cause of the pathological process in the bronchioles are respiratory diseases, COPD, bronchial asthma, damage to the respiratory tract by toxic substances. Bronchiolitis is a heterogeneous group of diseases that are less common than obstructive pulmonary disease or asthma, and are a manifestation of nonspecific reactions of lung tissue to damaging factors. The most common form of the disease is unilateral focal bronchiolitis. Unilateral bronchiolitis has a more favorable prognosis than the bilateral variant. Bilateral bronchiolitis often leads to the development of cardiopulmonary insufficiency. The diagnosis of the disease is carried out by examining the function of external respiration, bronchoscopy, bronchography, advanced computed tomography of the chest organs. Although the first description of bronchiolitis was made back in 1901 by V. Lange, the diagnosis and treatment of bronchiolitis remains a difficult task, perhaps because bronchiolitis is much less common compared to COPD or BA. Rheumatoid arthritis (RA) is one of the most common rheumatic diseases, affecting up to 1% of the adult population in the developed countries of the world. Little is known about the frequency of bronchiolitis in RA patients. The first descriptions of RA-associated bronchiolitis (RB) referred to isolated severe, rapidly progressive, often fatal cases. Respiratory organ damage (OD) is one of the most frequent extra-articular manifestations of rheumatoid arthritis (RA), which, according to some data, develops in 60-80% of patients with RA (Cortet B. et al., 1997; Turesson C. et al., 2003). The lesion associated with RA can occur at any level and with the involvement of almost all structures of the respiratory system: respiratory tract, lung parenchyma, serous membrane (Suda T., 2015), at the same time, the lesion pulmonary vessels are an extremely rare phenomenon (Fischer A., du Bois R., 2012).